EVALUASI PEMILU LEGISLATIF 2009 : Tinjauan atas Proses Pemilu, Strategi Kampanye, Perilaku Memilih, dan Konstelasi Politik Hasil Pemilu - Romli, Lili (Jurnal Penelitian Politik, 2010)
In general the 2009 legislative election has been conducted condusively However there were some problemsin the implementation ofthe election such asfixed voter lists and the election results decision In this election participation ofthe voter was decreasing relatively compare to previous election and the trend of the voter behaviourtend to be transactional In this regards there were frictions of the 2009 election results with the victory of theDemocratic Party accompanied by the decline of the Golkar Party PDIP and Islamic parties